Simulation of leaf area expansion of maize (Zea mays L.) under weed management practices using empirical models - Fakoor, Mohammad Yosuf; Parsa, Abdul Khalil Bizhan (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif 2007 at Main Research Station, UAS Hebbal, Bangalore to study cob growth pattern in maize using empirical models under different weed management practices. Quadratic and linear models were used for simulating leaf area expansion. Functional models were used using leaf area at 10 days interval from 10 to 120 DAS, under four weed management practices viz., (i) Atrazine, 0.75 kg ai/ha (eliminating competition of grassesand broad leaf weeds), (ii) 2, 4-D EE 0.8 kg ai/ha (eliminating competition from broad leaf weeds), (iii) Hand weeding at 20 and 40 DAS (eliminating all weed types competition) and (iv) Unweeded control (offering competition of all weed types). Fourth degree polynomial showed prediction of 88 to 98% in simulating course of leaf area expansion per unit leaf number in maize, while quadratic model showed prediction of 88 to 96% and linear model gave prediction of 74 to 88%. Differentiating quadratic and the linear functional models indicated that relative rate of leaf area expansion (RRLAE) (cm2/plant/day) was improved by 455.06 to 491 in hand-weeding or Atrazine application due to elimination of weed competition over unweeded control. Further, models worthiness by using linear and quadratic models in terms of relative rate of leaf area expansion in maize was higher with pre-emergence use of Atrazine or Oxyfluorfen at 3 DAS and was compared similar to hand weeding at (20 and 40 DAS).